IMPLEMENTASI METODE ANALYTICAL HIERARCHY PROCESS (AHP) DAN METODE PROFILE MATCHING DALAM KEPUTUSAN SELEKSI PEREKRUTAN TENAGA KURIR - Putri Nurul Amaliyah; Yusuf Ramadhan Nasution; Fakhriza Fakhriza (Universitas Gunadarma, 2023)
Recruitment or popularly known as recruitment is the process of selecting and sorting human resources to carry out company objectives. A Decision support system (DSS) is an alternative computer-based system that can assist organizations or companies in making structured and efficient decisions. Selecting employees with the needs and standards of company policy can be solved by the AHP method (Analytical Hierarchy Process) and PM (Profile Matching) by taking into account the data criteria of the company's employees. In this study, a combinaton of both methods to obtain a candidate courier is recommended. In the trial of five samples of potentital couriers to try calculation using the AHP and PM method applied to the requirement for potential J&T Batang courier personnel, the first alternative (A1) Budi Harsono had the highest value. Implementing this system using PHP Programming Language, HTML, CSS, Javascript and MySQL as a database management system.